Analisis Butir Soal Ujian Akhir Bentuk Pilihan Ganda Mata Pelajaran Bahasa Arab Kelas XI Madrasah Aliyah Negeri 2 Cilacap Tahun Pelajaran 2023/2024 - Audi Ismatul Mukarromah; Zamakhsari; Muhajir (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Assessment is a critical component of the learning process, serving to determine the achievement of learning objectives. This study aims to evaluate the quality of Arabic language multiple-choice final exam items for eleventh-grade students of class